In-situ observation of environmentally assisted crack initiation and short crack growth behaviour of new-generation 7xxx series alloys in humid air. (15th May 2023) - Euesden, R.T.; Aboura, Y.; Garner, A.J.; Jailin, T.; Grant, C.; Barrett, Z.; Engel, C.; Shanthraj, P.; Holroyd, N.J.H.; Prangnell, P.B.; Burnett, T.L.
Abstract: Large area, time resolved, in-situ optical scanning of constant displacement (four-point bend) tests has been used to monitor the environmentally assisted cracking (EAC) initiation and crack growth behaviour of AA7085 and AA7449 T7651 thick plate materials, exposed to warm-humid air (50 % RH & 70 °C). Subsequent fractography has revealed the dominant initiation sites originating at surface connected gas pore clusters, in combination with reactive Mg-containing constituent intermetallic compounds co-located on grain boundaries. Cracks were also shown to grow at stress intensities substantially below the KIEAC threshold measured via DCB testing, which should not therefore be taken as a limit below which EAC cannot occur. Highlights: In-situ optical monitoring was utilised to accurately identify EAC crack initiation sites in 7xxx aluminium alloys in humid air. High-resolution fractography found that cracks initiated at surface connected gas pores, sometimes in combination with Mg-rich IMC particles. Short cracks exhibited highly variable growth rates, reflecting the susceptibility of short crack growth to variation in local microstructure. Naturally nucleated short cracks can grow at stress intensities substantially below the KIEAC threshold, as measured from DCB tests.